Uso da realidade virtual no glaucoma - Daga, Fabio Bernardi [UNIFESP] (2020)
Objectives: To evaluate the use of virtual reality for assessment of functional loss in glaucoma patients. For this purpose, five studies were conducted with the following specific objectives: 1- To evaluate the impact of different hazardous traffic conditions on driving performance in glaucoma patients, as investigated in a high-fidelity driving simulator. 2- To investigate the frequency of mobile telephone use while driving and to assess whether patients with glaucoma had a disproportionate decrease in driving performance while conversing on a mobile telephone compared with normal controls. 3- To investigate the relationship between postural metrics obtained by dynamic visual stimulation in a virtual reality environment and the presence of fear of falling in glaucoma patients. 4- To investigate the impact of glaucomatous visual field loss on wayfinding behavior using an immersive virtual reality environment. 5- To describe the development and initial validation of a portable brain-computer interface for objectively assess visual function loss. Methods: Patients with glaucoma and normal controls were included in this line of research. They were tested in specific virtual reality tests and underwent a comprehensive ophthalmologic examination and visual field testing on standard automated perimetry. In addition, questionnaires were administered to patients. Results: The first study demonstrated that overall mean time to take the foot off the gas pedal and to depress the brake pedal was longer for glaucoma patients compared to controls (P=0.035 and P=0.005, respectively). In addition, glaucoma patients had longer RT for low saliency hazards compared with high saliency ones (P=0.020). The second study demonstrated longer RT to peripheral stimuli among patients with glaucoma compared with controls during mobile phone use (1.86 vs. 1.14 seconds, respectively; P=0.02). In the third study patients with glaucoma reported greater fear of falling compared to controls. Additionally, fear of falling was not associated with binocular standard perimetry mean sensitivity. On the other hand, the anteroposterior postural instability parameter during dynamic stimulus was associated with worse scores on the fear of falling questionnaire. On the fourth study glaucoma patients performed worse than controls for allocentric wayfinding task (35 vs. 24.2 seconds, respectively; P=0.001). In the fifth study the receiver operating characteristic curve area for the global parameter was 0.92, which was larger than for standard automated perimetry mean deviation (0.81). In addition, average intraclass coefficient for the global parameter (mean sector’s frequency) was 0.92. Conclusion: 1- The study demonstrated that RTs in response to hazardous driving situations were longer for glaucoma patients compared to controls. The results indicate that judgments about fitness to drive in glaucoma patients should not rely solely on the severity of visual field loss. 2- Patients with glaucoma should be informed that they may have a higher driving risk which could be even worsened by distractions, such as mobile telephone use. 3- In glaucoma patients, postural reactivity to a dynamic visual stimulus using a virtual reality environment was more strongly associated with fear of falling than visual field testing and traditional balance assessment. 4- Visual field loss may affect the construction of spatial cognitive maps relevant to successful wayfinding. 5- The device discriminated eyes with glaucomatous neuropathy from healthy eyes in a clinically based setting.